FORMS OF SOLIDARITY WITH NICARAGUA FROM COSTA RICA IN THE 20TH CENTURY: VARIATIONS ACROSS OCCUPATION, DICTATORSHIP AND REVOLUTION - Morales Bejarano, Siany (2025)
This paper examines the concept of solidarity by studying of the Costa Rican Solidarity Committee with Nicaragua, with special attention to its actors and practices between 1977 and 1984 in the context of the Sandinista Revolution. It also explores three earlier solidarity initiatives that emerged in Costa Rica during the 20th century: the Pro-Nicaragua Committee of 1923, the Pro-Sandino Committee of 1928, and the Pro-Free Nicaragua Committee of 1959. The study concludes that, in the 1920s, solidarity was expressed as support for the Nicaraguan people amid internal liberal-conservative conflicts as well as resistance to the U.S. occupation. In 1959, it focused on supporting Nicaraguan exiles opposing the dictatorship. During and after the Sandinista Revolution, solidarity took on more organized forms, combining humanitarian aid, awareness-raising campaigns, and direct participation in the revolutionary struggle. Across these periods, solidarity acquired multiple meanings, shaped by historical contexts and the social actors involved.